The Effect of Workload and Job Satisfaction on Employee Turnover Intention at P. Astra International Tbk-Tso Auto 2000 - Yosevina Gracia Manurung; Dionisius Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2023)
This Study Aims To Determine The Effect Of Workload And Job Satisfaction On Employee Turnover Intention At Pt. Astra International Tbk-Tso Auto 2000 Kisaran. The Sampling Technique In This Study Was Purposive Sampling With A Total Sample Of 56 Employees Of Pt. Astra International Tbk-Tso Auto 2000 Kisaran. The Data Collection Technique Of This Research Used An Instrument In The Form Of A Questionnaire In Which Each Statement Item Had Been Tested For Validity And Reliability. The Scoring Of The Answers To The Questionnaire Uses A Likert Scale. The Data Analysis Of This Study Used Linear Regression Analysis And Hypothesis Testing Using T Test, F Test And Coefficient Of Determination (R2) Which Was Carried Out With The Help Of Spss 21 Software For Windows. The Results Showed That Workload Had A Positive And Significant Effect On Turnover Intention As Evidenced By The Value Of Tcount Greater Than Ttable (5.577>2.00404). With A Significant Value (0.000<0.05). Job Satisfaction Has A Negative And Significant Effect On Turnover Intention As Evidenced By The Value Of Tcount Greater Than Ttable (-4,187 > 2,00488).